Asia-Pacific nursing scholarship development: Qualitative exploration of nurse scholars in Taiwan (Republic of China) - Sue Turale (2018)
Aim.: From the perspective of scholars, to describe a contemporary view of the development, facilitators of and barriers to nursing scholarship in Taiwan, to enhance policy-making about research, education and practise development. Background.: Nursing scholarship in the Asia-Pacific region is in different stages of development, depending on in-country resources and socio-economic conditions. Little is known about the facilitators or barriers to nursing scholarship in some of these countries, including Taiwan, where nursing education has changed considerably over the last decade. Design.: A qualitative exploratory design. Method.: The study used snowballing to identify scholars who underwent semi-structured in-depth interviews. These were digitally recorded, transcribed verbatim and subjected to content analysis. Results.: Interviews were held with 12 scholars and six major themes arose: 'fulfilling our missions'; 'active research productivity'; 'low levels of collaborative research'; 'increasing demands on time'; 'gender issues' and 'developing effective collaborative networks across Taiwan and Asia'. Participants described Taiwanese scholarship development in terms of fulfilling the missions of universities; trying to balance work and culturally relevant family responsibilities, against a background of decreasing pressures to produce more qualified nurses and being more research productive in rapidly changing and challenging work environments. Conclusions.: Taiwan's nursing scholarship is in a dynamic early stage of development, with increasing graduate programmes and research productivity, evidenced by rising international publications and the research productivity indexes of academics. However, scholars are facing increasing pressure because of high workloads and balancing family and work responsibilities. Relevance to clinical practice.: Understanding scholarship development and its facilitators and barriers in Taiwan helps inform policy makers, the higher education sector and nurses in the country and across the region about what needs to be done to improve nursing practice, raise health outcomes and enhance nursing research productivity and education. © 2010 Blackwell Publishing Ltd.